Segmentation-Guided Deep Learning for Glioma Survival Risk Prediction with Multimodal MRI - Jianhong Cheng; Hulin Kuang; Songhan Yang; Hailin Yue; Jin Liu; Jianxin Wang (Big Data Mining and Analytics)
Glioma survival risk prediction is of great significance for the individualized treatment and assessment programs. Currently, most deep learning based survival prediction paradigms rely on invasive and expensive histopathology and genomics methods. However, magnetic resonance imaging (MRI) has emerged as a promising non-invasive alternative with significant prognostic potential. To leverage the benefits of MRI, we propose a segmentation-guided fully automated multimodal MRI-based survival network (SGS-Net), which can simultaneously perform glioma segmentation and survival risk prediction. Specifically, the task interrelation is addressed using a hybrid convolutional neural network-Transformer (CNN-Transformer) encoder to represent the shared high-level semantic features by co-training a decoder for glioma segmentation and a Cox model for survival prediction. Then, to ensure the effective representation of the high-level features, glioma segmentation as an auxiliary task is utilized to guide survival prediction by jointly optimizing the segmentation loss and the Cox partial log-likelihood loss. Furthermore, a pair-wise ranking loss is designed to allow the network to learn the survival difference between patients. To balance the multi-task losses, an uncertain weight manner is adopted to adaptively adjust the weights for preventing task bias. Finally, the proposed SGS-Net is assessed using a publicly available multi-institutional dataset. Experimental and visual results show that SGS-Net achieves promising segmentation performance and obtains a C-index of 81.07% for survival risk prediction, which outperforms several existing state-of-the-art methods and even histopathology-based methods. In addition, Kaplan-Meier survival analysis confirms that the prognosis risk generated by SGS-Net is consistent with the prior prognosis based on the grading or genotyping paradigms.